State, communities and forests in contemporary Borneo - Cooke, Fadzillah M. (Asia-Pacific environment monograph, 2006)
"This book, the first in the series of Asia-Pacific Environmental Monographs, looks at the political complexities of forest management across the whole island of Borneo, tackling issues of tenure, land use change and resource competition, 'tradition' versus 'modernity', disputes within and between communities, between communities and private firms, or between communities and governments. While it focuses on the changes taking place in local political economies and conservation practices, it also makes visible the larger changes taking place in both Indonesia and Malaysia. The common theme of the volume is the need to situate local complexities in the larger institutional context, and the possible gains to be made from such an approach in the search for alternative models of conservation and development."--Publisher's description